Building on PIM COVID-19 research, PIM modeling tools are used to inform ranking of policy investments and identification of priority value chains in Nigeria - CGIAR Research Program on Policies, Institutions, and Markets (2020)
PIM researchers conducted an analysis of COVID-19 impacts on Nigeria’s food systems. The information-gathering process, dissemination of initial findings and discussions with stakeholders led to a demand from the Government to use PIM tools to inform planning for Nigeria’s Medium-Term National Development Policy for target years 2025, 2030, and 2050 and for the Nigeria Agenda 2050.